Cdc25M2 activation of cyclin-dependent kinases by dephosphorylation of threonine-14 and tyrosine-15. - Sebastian, B (1993)
Recent evidence has suggested that human cyclin-dependent kinase 2 (CDK2) is an essential regulator of cell cycle progression through S phase. CDK2 is known to complex with at least two distinct human cyclins, E and A. The kinase activity of these complexes peaks in G1 and S phase, respectively. The vertebrate CDC2/cyclin B1 complex is an essential regulator of the onset of mitosis and is inhibited by phosphorylation of CDC2 on Thr-14 and Tyr-15. In vitro, CDC2/cyclin B1 is activated by treatment with the members of the Cdc25 family of phosphatases. We found that, like CDC2, CDK2 is also phosphorylated on Thr-14 and Tyr-15 and that treatment of cyclin A or cyclin E immunoprecipitates with bacterially expressed Cdc25M2 (the mouse homolog of human CDC25B) increased the histone H1 kinase activity of these immune complexes 5- to 10-fold. Tryptic peptide mapping demonstrated that Cdc25M2 treatment of cyclin A or cyclin B1 immune complexes resulted in the specific dephosphorylation of Thr-14 and Tyr-15 on CDK2 or CDC2, respectively. Thus, we have confirmed that Cdc25 family members comprise a class of dual-specificity phosphatases. Furthermore, our data suggest that the phosphorylation and dephosphorylation of CDKs on Thr-14 and Tyr-15 may regulate not only the G2/M transition but also other transitions in the cell cycle and that individual cdc25 family members may regulate distinct cell cycle checkpoints.